Operationalizing Essential Characteristics of Creativity in a Computational System for Music Composition - Bodily, Paul M.; Ventura, Dan (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
We address the problem of building and evaluating a computational system whose primary objective is creativity. We illustrate seven characteristics for computational creativity in the context of a system that autonomously composes Western lyrical music. We conduct an external evaluation of the system in which respondents rated the system with regard to each characteristic as well as with regard to overall creativity. Average scores for overall creativity exceeded the ratings for any single characteristic, suggesting that creativity may be an emergent property and that unique research opportunities exist for building CC systems whose design attempts to comprehend all known characteristics of creativity.